Early childhood research & practice ECRP.
Intended for researchers, teacher educators, program planners, policy- and decision-makers, administrators, practitioners, and parents. Early Childhood Research & Practice (ECRP) features articles relating to thedevelopment, care, and education of children from birth to approximately age 8.